Coaker film rushes : Interview with Mr. Josiah Kearley. Part 1 - Memorial University of Newfoundland. Extension Service (Producer) (Memorial University of Newfoundland. Extension Service, 1970)
Mr. Josiah (Joe) Kearley speaks about William Coaker, the Orange Lodge and the local Orange Hall itself along with Coaker's involvement in the Fishermen's Union. Condition: video ends abruptly